Study the Effect of Interleukin36 Gamma and AMH in Iraqi Women with PCOS - Wafa R. AlFatlawi (Al-Mustansiriyah Journal of Science, 2018)
Polycystic ovary syndrome (PCOS) is one of the most common female endocrine disorders and affect approximately (5-10) % of women of reproductive age. Anti-Müllerian hormone (AMH) is a homodimeric glycoprotein, a member of the transforming growth factor-β superfamily, it is secreted exclusively from women by granulose cells of ovarian follicles and it is considered as the precise marker of follicle pool size. AMH has been shown to be a good surrogate marker for polycystic ovary syndrome (PCOS). Interleukins are considered as strong risk markers of inflammation. Interleukin-36 gamma (IL36) also known as interleukin-1 family member 9 (IL1F9) is a protein that in humans is encoded by the IL36G gene. Serum samples were collected on day 2 of the menstrual cycle. Serum IL36ɣ, FSH and LH concentration were measured by using ELISA. This study aimed to evaluate the association between IL36ɣ and AMH and study the relationship between obesity and AMH of women in the age of reproductive (25-35) yrs. This study included 28 infertile women with PCOS their husbands were apparently normal (hormones and seminal fluid analysis), their aged (25-35) years, and 20 healthy women aged (25-33) years as control. All control women & patients were from outpatients unit of Alkadumia teaching hospital at Baghdad and all the parameters were measured in Sigma Laboratory. Serum IL-36 ɣ elevated in PCOS patients mainly those with high AMH levels. This hormone increased in PCOS patients compared with control. There was a non-significant difference between patients and control to LH and FSH levels.